ELECTROCARDIOGRAM ST SEGMENT DEPRESSION AND ELEVATION IN STRESS-TESTING - D. A. Kuzhel; G. V. Matyushin; T. D. Fedorova; N. V. Kovaleva; E. A. Savchenko; S. E. Golovenkin (Столичная издательская компания, 2015)
The electrocardiogram remains a crucial tool for the identification of myocardial ischemia. Important information for patient management and prognosis determination can be derived from the stress testing electrocardiogram. Leads with ST-segment elevation indicate the ischemia related coronary artery.